Plan de marketing para el desarrollo turístico de la parroquia El Progreso, cantón Pasaje. - Jordan Alban, Maria Katherine; Campoverde Miranda, Kristhel Sarely (Machala : Universidad Técnica de Machala, 2024)
The present degree project aims to develop a marketing plan for tourism development in the parish of El Progreso, in order to disseminate and promote its attractions for tourism development. With the implementation of effective digital marketing strategies, we seek economic growth, improved visibility and influx of tourists. The research is based on a mixed approach that combines qualitative and quantitative methodologies, through the observation of attractions and information gathering, the application of surveys to tourists and service providers, and interviews with local governance. The results reflect a low promotion of these attractions, as well as a limited management of marketing strategies focused especially in this parish of the Pasaje canton. The proposal consists of a marketing plan focused on the creation of a web page containing information about the parish of El Progreso to promote its natural and cultural tourist attractions, as well as providing information such as its accessibility, gastronomy, festivities, customs and traditions, among others, based on this to promote its diffusion as a tourist potential of the canton. This proposal seeks not only to increase tourism in the area, but also to promote the economic development of the parish.
El presente trabajo de titulación tiene como objetivo realizar un plan de marketing para el desarrollo turístico de la parroquia el Progreso, con el propósito de difundir y promocionar sus atractivos para su desarrollo turístico. Con la implementación de estrategias efectivas de marketing digital se busca el crecimiento económico, mejora de visibilidad y afluencia de turistas. La investigación se basa en un enfoque mixto que combina metodologías cualitativas y cuantitativas, mediante la observación de atractivos y recopilación de información, la aplicación de encuestas a turistas y prestadores de servicios, entrevista a la gobernanza local. Los resultados reflejan una baja promoción de estos atractivos, así como una gestión limitada de estrategias de marketing enfocadas especialmente en esta parroquia del cantón Pasaje. La propuesta consiste en un plan de marketing enfocado en la creación de una página web que contenga información de la parroquia El Progreso para promocionar sus atractivos turísticos tanto naturales como culturales, además de brindar información como su accesibilidad, gastronomía, festividades, costumbres y tradiciones entre otros, en base a ello promover su difusión como potencial turístico del cantón. Esta propuesta busca no solo incrementar el turismo en la zona, sino también fomentar el desarrollo económico de la parroquia.
Keywords: TURISMO; PLANIFICACIÓN TURÍSTICA; MARKETING TURÍSTICO; PLAN DE MARKETING